Analysis of Zoom Meeting User Behavior Using Technology Acceptance Model Approach - Safaria, Siti; Rachmad, Ari (Ridwan Institute, 2024)
This study aims to determine the level of acceptance of respondents to the Zoom Meeting application in daily use during the pandemic with the Technology Acceptance Model (TAM) approach and to determine the behavior of users of the application related to perceived usefulness, perceived ease of use, attitude toward using, and behavioral intention. Respondents in this study were taken by random sampling technique. This research is a quantitative descriptive study, the data analysis tool in this study uses Smart PLS 3.0 Software and uses the Structural Equation Model (SEM) model. The results of this study are the level of acceptance of using the Zoom Meeting application for daily needs is influenced by the ease of accessing the application and the perceived benefits of use. In addition, it was found that there was a significant effect between the PU variables on ATU, PEU on ATU, PU on BI, ATU on BI, and there was an indirect effect between the PU variables on BI through ATU as an intervening variable. However, the ATU variable cannot mediate the relationship between PEU and BI.